Elements of the jurisdiction of the future: A web experience, a proposal and a vision - Jiménez Vivas, Javier Eduardo (2020)
The tools of the internet are increasingly influencing society, law and the jurisdictional function (even more so in the context of the SARS-CoV-2 pandemic). The impact of the first web generation was overwhelming, but the second generation offers advantages and specifications which it seems will not be detected or appreciated in the future, despite its potential to produce public value and to build a new relationship between justice and society. In this sense, this article explains the proposed digital transformation that has taken place between 2017 and 2020 (basis, purpose, and projection). Finally, we will set out our vision for the future of organizational, digital, and social transformation.